2012
DOI: 10.1186/2192-1121-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Mobile communication for intellectually challenged people: a proposed set of requirements for interface design on touch screen devices

Abstract: The use of certain applications for touch-based mobile devices can prove to be difficult for intellectually challenged people. By performing tests and gathering user feedback, great difficulty has been detected in the use of various applications due to their complicated interfaces. The authors propose a set of guidelines, aimed at developers, to help design more accessible interfaces when developing applications for intellectually challenged, so this might increase the overall ease of use of mobile devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…swiping up, rather than across) and these barriers have been noted previously in the literature (e.g. De Urturi Breton et al, 2012). While literature suggests that mobile phone use is common for people with intellectual disability (Bryen et al, 2007) Future studies should focus on improving the survey content, layout, language and use of images.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…swiping up, rather than across) and these barriers have been noted previously in the literature (e.g. De Urturi Breton et al, 2012). While literature suggests that mobile phone use is common for people with intellectual disability (Bryen et al, 2007) Future studies should focus on improving the survey content, layout, language and use of images.…”
Section: Discussionmentioning
confidence: 82%
“…The Flesch–Kincaid readability test (Kincaid, Fishburne, Rogers, & Chissom, 1975) showed that the grade level of the survey questions was 0.8. To accommodate for literacy skills of adults with intellectual disability and to help counter the mobile device access issues noted in the literature (De Urturi Breton et al., 2012), the present authors specifically used an ESM survey application mEMA (Ilumivu, 2017) that allowed the use of images to assist the understanding of questions and response options; Figure 1 provides an illustrative example of the types of questions and the use of images in the survey. A full copy of all survey items and images is available from the corresponding authors upon request.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors explain the reasons of less frequent use of mobile phones in people with ID by expense, lack of perceived need, and difficulty in use. Furthermore, de Urturi Breton, Hernández, Zorrilla, & Zapirain (2012) concluded that the less frequent use of mobile phones in people with ID can be explained by inappropriate size of buttons, non-user-friendly menu arrangement, and insufficiently clear instructions as significant reasons.…”
Section: Discussionmentioning
confidence: 99%
“…However, the acceptability of these solutions among older individuals has been suggested as a limiting factor [ 31 ]. People with intellectual disabilities also face great difficulty using the complicated interfaces of modern SP-based applications [ 101 , 102 ]. A recent study has revealed the myth that older people avoid new technologies is a fallacy [ 103 ].…”
Section: Discussionmentioning
confidence: 99%